Financial Distortions in China : A General Equilibrium Approach - Anzoategui, Diego (IMF Working Papers; Working Paper ;, 2015)
Widespread implicit guarantees and interest ceilings were major distortions in China's financial system, contributing to a misallocation of resources. We analyze the impact of removing such frictions in a general equilibrium setting. The results show that comprehensive reforms generate better outcomes than partial ones: removing the deposit rate ceiling alone increases output, but the efficiency of capital allocation does not improve. Removing implicit guarantees improves output through lower cost of capital for private companies and better resource allocation.